Genome-wide association and transcriptomic analysis and the identification of growth-related genes in Macrobrachium nipponense - Zijian Gao; Wenyi Zhang; Sufei Jiang; Hui Qiao; Yiwei Xiong; Shubo Jin; Hongtuo Fu (BMC Genomics, 2024)
Abstract Macrobrachium nipponense is a commercially important freshwater species of prawn that is widely distributed across Asian countries. In order to investigate the molecular mechanisms of growth in M. nipponense, and to provide a foundation for molecular breeding, we used genome-wide association analysis (GWAS) and transcriptomic analysis to screen polymorphisms and genes related to growth traits. We recorded the growth traits of 100 adult M. nipponense at the same growth stage, and each individual genotype was evaluated by whole genome resequencing. GWAS of growth traits detected 12 growth-related single-nucleotide polymorphisms (SNPs) and eight growth-related genes from 49 chromosomes. Of the 100 individuals, we sampled muscle tissue from a total of 18 female and male M. nipponense exhibiting large differences in growth rate for RNA-seq. Transcriptome analysis revealed a total of 27,996 unigenes; of these, 33 and 60 differentially expressed genes were identified from males and females, respectively. Of these, 12 genes associated with energy metabolism and cytoskeletal pathways were identified as growth-related genes. Notably, genes from the actin family and the ubiquitin C-terminal hydrolase 2 (UCH2) gene were identified by both GWAS and transcriptomic analysis. Two growth-related SNPs, S40_12327385 and S40_12327391, were found to be mapped to the ACTB gene. The ACTA1 gene, also from the actin family, was up-regulated in fast-growing males and females, while the ACT57B was down-regulated. In addition, the growth associated SNP S7_35313774 was located in the UCH2 gene; transcriptomics analysis revealed that the UCH2 gene was up-regulated in female individuals exhibiting high growth rates. Overall, our results provided a set of markers and candidate genes related to the growth of M. nipponense. These findings could facilitate the breeding management of this species and help us to further understand the genetic mechanisms of growth in crustaceans.